Горе от ума - Грибоедов Александр Сергеевич (Классика в школе, 2015)
Экземпляры: с/ф № 4 (20150707) / Инвентарный номер: 44002 / Цена: / Сис.шифр: 84(2Рос=Рус)1 / Авт.знак: Г 82 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)1